2016
DOI: 10.1113/ep085347
|View full text |Cite
|
Sign up to set email alerts
|

Raised arterial blood pressure in neurokinin‐1 receptor‐deficient mice (NK1R−/−): evidence for a neural rather than a vascular mechanism

Abstract: New Findings r What is the central question of this study?Does genetic ablation of neurokinin-1 receptors alter arterial blood pressure? r What is the main finding and its importance? NK1R−/− mice have increased mean arterial blood pressure, but without a concomitant change in vascular reactivity. This finding suggests that neurokinin-1 receptors play a role in the neural regulation of blood pressure.Mice with functional ablation of the neurokinin-1 receptor gene, Tacr1, (NK1R −/− ) express behavioural abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Yet, endothelial NK1R activation can also result in thromboxane-mediated vasoconstriction ( Figure 4 ). Interestingly, global knockout of the NK1R gene ( Tacr1 ) resulted in no alteration to vascular function in isolated systemic arteries ( Moyes et al, 2016 ). Given that both smooth muscle and endothelial cells were lacking NK1R in these mice, it may explain the phenotype.…”
Section: Investigation Of C-fiber-derived Neuropeptides As Novel Pulmmentioning
confidence: 99%
“…Yet, endothelial NK1R activation can also result in thromboxane-mediated vasoconstriction ( Figure 4 ). Interestingly, global knockout of the NK1R gene ( Tacr1 ) resulted in no alteration to vascular function in isolated systemic arteries ( Moyes et al, 2016 ). Given that both smooth muscle and endothelial cells were lacking NK1R in these mice, it may explain the phenotype.…”
Section: Investigation Of C-fiber-derived Neuropeptides As Novel Pulmmentioning
confidence: 99%
“…We could show a substance P-dependent sympatho-inhibitory control circuit via afferent nerves even under healthy conditions [14]. Mice lacking NK1 receptors have an increased blood pressure [40]. The authors, who examined these mice, assumed a neurogenic mechanism rather than a change in vascular reactivity of these mice.…”
Section: Sp-importance For Trpv1 Sensitizationmentioning
confidence: 92%
“…First, comparisons of the locomotor behaviour of NK1R-/- mice and their wildtypes have revealed that the former genotype typically displays locomotor hyperactivity in a range of different experimental settings (Fisher et al, 2007; Herpfer et al, 2005; Moyes et al, 2016; Porter et al, 2015a, 2015b). …”
Section: Introductionmentioning
confidence: 99%